Long‐term impact of hydrological regime on structure and functions of microbial communities in riverine wetland sediments. Issue 2 (4th April 2013) - Foulquier, Arnaud; Volat, Bernadette; Neyra, Marc; Bornette, Gudrun; Montuelle, Bernard
Abstract: In a context of global change, alterations in the water cycle may impact the structure and function of terrestrial and aquatic ecosystems. Wetlands are particularly at risk because hydrological regime has a major influence on microbially mediated biogeochemical processes in sediments. While the influence of water availability on wetland biogeochemical processes has been comprehensively studied, the influence of hydrological regime on microbial community structure has been overlooked. We tested for the effect of hydrological regime on the structure and functions of microbial communities by comparing sediments collected at multiple sites in the Ain département (Eastern France). Each site consisted of two plots, one permanently and one seasonally inundated. At the time of sampling, all plots were continuously inundated for more than 6 months but still harboured distinct bacterial communities. This change in community structure was not associated with marked modifications in the rates of microbial activities involved in the C and N cycles. These results suggest that the observed structural change could be related to bacterial taxa responding to the environmental variations associated with different hydrological regimes, but not strongly associated with the biogeochemical processes monitored here.